2015
DOI: 10.1007/s00330-015-3975-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast-enhanced modified T1-weighted 3D TSE black-blood and 3D MP-RAGE sequences for the detection of cerebral metastases and brain tumours

Abstract: • T1-mVISTA leads to significantly higher contrast-to-noise ratios of cerebral malignomas. • T1-mVISTA detects significantly more metastatic lesions compared to 3D-MPRAGE. • Lesions detected only by T1-mVISTA are smaller than those detected in both sequences. • Diagnostic confidence is significantly higher for lesions detected by T1-mVISTA. • Application of T1-mVISTA might be of high relevance in early stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…Our findings are in line with recent studies, that obtained higher detection rates for brain lesions using T1-DB sequences compared to the routinely used T1w-SE or T1w-GRE sequences. [ 14 , 15 ] However, we did not compare between T1-DB and T1w-SE but T1w-MPRAGE, which is a 3D gradient echo sequence with an initial 180 degree inversion pulse and routinely used in our institution as standard sequence for CEL detection in MS patients. While it is reported that T1w-SE shows better sensitivity of contrast enhancement than T1w-GRE at 1.5 T, it is also prone to flow related artefacts and is usually acquired in thicker slices, since covering the whole brain in thin slices would take too much time in clinical routine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with recent studies, that obtained higher detection rates for brain lesions using T1-DB sequences compared to the routinely used T1w-SE or T1w-GRE sequences. [ 14 , 15 ] However, we did not compare between T1-DB and T1w-SE but T1w-MPRAGE, which is a 3D gradient echo sequence with an initial 180 degree inversion pulse and routinely used in our institution as standard sequence for CEL detection in MS patients. While it is reported that T1w-SE shows better sensitivity of contrast enhancement than T1w-GRE at 1.5 T, it is also prone to flow related artefacts and is usually acquired in thicker slices, since covering the whole brain in thin slices would take too much time in clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 13 ] Furthermore, in recent studies it was demonstrated that at 1.5 Tesla, T1-DB sequences were superior to T1w-SE detecting brain lesions such as primary central nervous system malignant neoplasia and metastases. [ 14 , 15 ] However, these former studies included a small heterogeneous group of potential contrast enhancing lesions and, so far, no study exists examining the potential of T1-DB sequences for CEL detection in a larger homogeneous population or MS. We therefore chose a population of MS patients, where the detection, number and volume of contrast-enhancing lesions is relevant in the diagnostic work-up and is used as endpoint in therapy studies. With the promising results of the recently published studies we hypothesized, that post-contrast T1-DB sequences detect more enhancing MS lesions than the routinely used T1w-GRE with superior inter-observer agreement.…”
Section: Introductionmentioning
confidence: 99%
“…24 We recently developed a novel 3D T1w TSE BB sequence with variable refocusing flip angles sweeps (T1-weighted modified volumetric isotropic TSE acquisition [T1-mVISTA]). 25 This sequence provides a submillimeter isotropic resolution, coverage of the whole brain, reconstruction in all planes, and scan times under 5 minutes. In an initial study in patients with cerebral metastases, detection rates with T1-mVISTA were nearly doubled, especially in small lesions under 5 mm.…”
mentioning
confidence: 99%
“…While conventional turbo field echo (TFE) imaging before and after contrast administration has been long established to assess tumor-related contrast enhancement and spread, recent studies have hinted at the value of advanced T1-weighted sequences for the depiction of intracranial contrastenhancing pathology [19,20]. Although initially developed for vessel wall imaging, T1-weighted black blood (BB) sequences in particular have gained attention for depicting intracranial malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Although initially developed for vessel wall imaging, T1-weighted black blood (BB) sequences in particular have gained attention for depicting intracranial malignancies. Recently, MRI protocols making use of contrast-enhanced (CE) BB sequences were able to detect significantly more cerebral metastases and had a higher sensitivity to identify leptomeningeosis carcinomatosa compared with more established T1-weighted sequences for this purpose (e.g., gradient echo and spin echo sequences) [19,21].…”
Section: Introductionmentioning
confidence: 99%